YWHAH Genetic Variants are Associated with Increased Hypoxia Inducible Factor-1α/Vascular Endothelial Growth Factor in Egyptian Rheumatoid Arthritis Patients - Fattah, Shaimaa A.; Fattah, Maha A. Abdel; Mesbah, Noha M.; Saleh, Samy M.; Abo-Elmatty, Dina M.; Mehanna, Eman T. (Biochemical genetics, 2022)
The 14–3-3 Eta (14–3-3 η) biomarker platform is a relatively recent discovery with the potential to significantly address the diagnosis and prognosis of rheumatoid arthritis (RA) disease. Hypoxia-inducible factor (HIF)-1α and vascular endothelial growth factor (VEGF) have been implicated in inflammatory mechanisms in RA. We hypothesized a molecular association of the coding YWHAH gene and its expressed protein 14–3-3 η with hypoxia and angiogenesis in RA. One hundred healthy subjects and 100 RA patients were enrolled in the study. YWHAH gene expression was determined using quantitative PCR, and its gene polymorphism rs2858750 was assessed by Taqman genotyping assay. Serum levels of 14–3-3 η, HIF-1α, and VEGF were measured using the ELISA technique, and clinical parameters were routinely examined. In RA patients, significant positive correlations were found between 14–3-3 η, HIF-1α ( r = 0.84), and VEGF ( r = 0.85). YWHAH gene expression was upregulated 10.8 fold (CI 95% 10.1–11.5) in RA patients and significantly correlated with all disease activity parameters, ACPA, and levels of 14–3-3 η, HIF-1α, and VEGF. RA patients showed a higher frequency of YWHAH rs2858750 A allele than healthy subjects ( p = 0.02). The risk A allele carriers showed higher disease activity parameters, ACPA, YWHAH gene expression, and increased serum levels of 14–3-3 η ( p < 0.001), HIF-1α ( p = 0.002), and VEGF ( p = 0.001) than the G allele. Serum 14–3-3 η and its rs2858750 genetic variant are associated with increased hypoxia and angiogenesis in RA and activity, and severity of the disease. Graphical Abstract